Assessing training needs of primary care pharmacists: a cross-sectional survey in China - Qingran Sun; Yanan You; Kejia Cao; Yuankai Huang; Xiaoyu Xi (BMC Medical Education)
Abstract Background Training can significantly improve the knowledge and skills of pharmacists. Previous study showed that there is a large gap in the training of pharmacists across countries. Primary healthcare workers did not have enough opportunities to trainings in China. This study aimed to explore the current status of training content, training approaches and unmet training needs from the perspective of primary care pharmacists. Method A multi-stage sampling method was used to conduct a questionnaire survey to collect the basic characteristics of primary medical institutions and pharmacists, the current status of primary care pharmacists’ training content and training approaches, and the unmet training needs. Descriptive statistics was used to report characteristics of the sample and paired chi-square test was used to test whether the training contents and training approaches meeting the needs of primary care pharmacists. Results Most of primary care pharmacists enter the field of pharmacy by receiving pharmaceutical education in colleges and universities, and have obtained professional title qualification and licensed pharmacist qualification certificate. The annual income and proportion of the pharmacists of bachelor degree or above in eastern and western parts are higher than the central region, and the difference was statistically significant. About 67.9% of the surveyed pharmacists received training less than once a year. There was statistically difference between current and expected training content and approach of primary pharmacists, showing that the group is still obviously has unmet training demands. The training contents of “clinical pharmacy knowledge, ability to deal with and analyze problems, and skills to provide pharmaceutical services” and the training mode of “further education in school” are the direction of development of the future training of primary care pharmacists. Conclusion The education and training of primary care pharmaceutical professionals in China have achieved initial success. This study identified the basic parts and future direction of development of training content and training form for primary care pharmaceutical professionals. The results of this study can be used as a basis for further development and research into the requirements of on-the-job training and continuing education for pharmacists.